Brucellous withers hygromae in beef cattle and sanitary measures at slaughtering - Langenegger, Jerome; Secchin, Haroldo; Baptista, Anna Maria (Pesquisa Agropecuaria Brasileira, 2014)
Brucellous withers hygromae were determined in 17 of 30.941 bovines slaughtered during the course of one year in Rio de Janeiro. The infection was demonstrated by use isolation of Brucella abortus and/or by a high agglutinine titre in the exudate from the Bursa cucullaris. Typing ten strains which were isolated, 4 were shown to belong to biotype 1 and 6 of the biotype 3 of Brucella abortus. Measures are proposed to prevent or minimize infection to humans in the slaughterhouses or by contamination of the meat occurring when the hygromae lacerate when sawing the carcass.
Keywords: Brucellosis; Brucella abortus biotype 3; Bursa cucullaris; hygroma; Brucella infection